2017
DOI: 10.2519/jospt.2017.6336
|View full text |Cite
|
Sign up to set email alerts
|

Trunk and Shank Position Influences Patellofemoral Joint Stress in the Lead and Trail Limbs During the Forward Lunge Exercise

Abstract: Study Design Controlled laboratory study, repeated-measures design. Background The effects of trunk and shank position on patellofemoral joint stress of the lead limb have been well studied; however, the effects on the trail limb are not well understood. Objectives To test the hypothesis that trunk and shank position may influence patellofemoral joint stress in both limbs during the forward lunge exercise. Methods Patellofemoral kinetics were quantified from 18 healthy participants performing the lunge exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In this study, the reduced hip flexion angle was achieved by leaning backwards with the trunk, which resulted in a posterior shift of the centre of mass. This strategy is known to unload the knee joint of the leading leg [Riemann et al 2012, Hofmann et al 2017. However, kinetics are needed to further evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the reduced hip flexion angle was achieved by leaning backwards with the trunk, which resulted in a posterior shift of the centre of mass. This strategy is known to unload the knee joint of the leading leg [Riemann et al 2012, Hofmann et al 2017. However, kinetics are needed to further evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Precedent studies on the forward lunge have reported that greater load being exerted on the knee joint of the front leg is affected significantly by the anterior movement of the upper torso and lower leg (Farrokhi et al, 2008;Hofmann et al, 2017). The load that is exerted on the front knee in the downward phase increases eccentric contraction of the quadriceps and knee extension moment, which increases the shear force of the ACL (Ekstrom et al, 2007;Yu & Garrett, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A forward lunge motion that is performed by striding one foot forward shifts the center of gravity forward as the knee joint in the front leg flexes after touching down on the ground surface, which has been used as the load in rehabilitation exercise and muscle strengthening training for the thighs and hip muscles (Hofmann et al, 2017;Park et al, 2010). Accordingly, the present study set the targeted knee flexion angles to 80°, 90°, and 100° and analyzed the reaction force, moment, and range of motion in the knee joint at the point of targeted knee flexion angle, as well as peak reaction force and moment generated in upward and downward phases for the objective of analyzing the effects of changes in the knee flexion angles during the forward lunge on the kinetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have examined patellofemoral biomechanics during the lunge exercise, [3][4][5] patellofemoral force and stress has been examined only once in the literature during the side lunge exercise 6 and only twice in the literature during the forward lunge exercise. 7,8 Escamilla and colleagues 7 employed a 12 repetition maximum (12 RM) weight to assess patellofemoral force and stress while performing the forward lunge using a long step and short step. In addition, Escamilla and colleagues 6 employed a 12 repetition maximum (12 RM) weight to assess patellofemoral force and stress between the forward lunge and the side lunge, and both patellofemoral force and stress were greater in the side lunge compared to the forward lunge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Escamilla and colleagues 6 employed a 12 repetition maximum (12 RM) weight to assess patellofemoral force and stress between the forward lunge and the side lunge, and both patellofemoral force and stress were greater in the side lunge compared to the forward lunge. Hofmann and colleagues 8 examined patellofemoral force and stress for both the lead and trail limb while performing the forward lunge with no external resistance between forward and vertical trunk and shank positions.…”
Section: Introductionmentioning
confidence: 99%